Lateral Angular Co-Extrusion: Geometrical and Mechanical Properties of Compound Profiles - Thuerer, Susanne Elisabeth; Peddinghaus, Julius; Heimes, Norman; Bayram, Ferdi Caner; Bal, Burak; Uhe, Johanna; Klose, Christian; Thürer, Susanne Elisabeth (MDPI, 2020)
A novel co-extrusion process for the production of coaxially reinforced hollow profiles has been developed. Using this process, hybrid hollow profiles made of the aluminum alloy EN AW-6082 and the case-hardening steel 20MnCr5 (AISI 5120) were produced, which can be forged into hybrid bearing bushings by subsequent die forging. For the purpose of co-extrusion, a modular tooling concept was developed where steel tubes made of 20MnCr5 are fed laterally into the tool. This LACE (lateral angular co-extrusion) process allows for a variation of the volume fraction of the reinforcement by using steel tubes with different wall thicknesses, which enabled the production of compound profiles having reinforcement contents of either 14 vol.% or 34 vol.%. The shear strength of the bonding area of these samples was determined in push-out tests. Additionally, mechanical testing of segments of the hybrid profiles using shear compression tests was employed to provide information about the influence of different bonding mechanisms on the strength of the composite zone.
Bayram, Ferdi Caner/0000-0002-8607-2421; Peddinghaus, Julius/0009-0001-9881-0110; Thurer, Susanne/0000-0003-4704-7028; Klose, Christian/0000-0002-5341-8457; Mohnfeld, Norman/0000-0002-9600-6209; Uhe, Johanna/0000-0002-4320-5570; Maier, H. J./0000-0003-2119-824X
Keywords: Tailored Forming; Lateral Angular Co-Extrusion; Mechanical Behavior; Hybrid Metal Components